Omnichannel Marketing Strategy to Increase Customer Satisfaction and Loyalty in Beverage MSMEs in Mojokerto Regency - Ina Dwi Wijayanti; Edwin Pondi Suwanto (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The rapid development of digital technology has transformed consumer purchasing behavior in the food and beverage sector by enabling purchases through multiple online and offline channels. This condition requires Micro, Small, and Medium Enterprises (MSMEs) to implement integrated marketing strategies to improve customer satisfaction and loyalty. This study aims to analyze the effect of omnichannel marketing strategies on customer satisfaction and customer loyalty in beverage MSMEs in Mojokerto Regency, Indonesia. A quantitative approach with a survey method was used, involving 130 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using SPSS through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²). The results show that all research instruments were valid and reliable. Omnichannel marketing has a positive and significant effect on customer loyalty, with a regression coefficient of 0.421 and a t-value of 5.872 (p < 0.05). Customer satisfaction also has a positive and significant effect on customer loyalty, with a regression coefficient of 0.389 and a t-value of 5.214 (p < 0.05). Simultaneously, omnichannel marketing and customer satisfaction significantly influence customer loyalty, as indicated by an F-value of 74.321 and a significance level of 0.000. The R² value of 0.681 indicates that 68.1% of customer loyalty variation is explained by both variables.